Pengembangan Kecerdasan Spiritual Santri Melalui 4B (Belajar-Berkolaborasi-Beraksi-Berbagi) di Lingkungan Pendidikan Berbasis Pesantren - Zainal Abidin; Imaduddin (Adabuna)
Spiritual intelligence is an urgent matter in the education system. That is because spiritual intelligence is a moral span to maintain the harmony of human life. The results of this study indicate that spiritual intelligence is built on four stages, namely (1) learning, namely exploring useful values for students, both religious values or social values, (2) collaborating, namely being involved in various activities held by the school, (3) acting, is the actualization of values embodied in daily activities as an illustration of spiritual intelligence, (4) sharing, is sharing knowledge and experience on an achievement gained, or an interesting experience in school. The pesantren system also reinforces religious values as a basis for considering meaning.